Knowledge of body mass index and its correlates among the patient at a tertiary care hospital - Lodha, Mahendra; Badkur, Mayank; Puranik, Ashok; Chaudhary, Ramkaran; Rodha, Mahaveer S.; Satya, Prakash; Kompally, Prathyusha (International Journal of Research in Medical Sciences, 2020)
Background: In spite of the numerous chronic diseases that have been linked to obesity, studies focusing on awareness regarding Body mass index (BMI) and its correlates to prevent and control obesity are lacking in the literature, especially in developing countries such as India, where obesity is culturally accepted and nurtured in the society. Methods: A cross-sectional prospective survey was done between November 2018 and November 2019 in a tertiary care research institute after approval from institutional ethics committee. A pre-designed questionnaire was used to collect data in excel sheet (Microsoft Corp, Redmond, WA) and analysed using SPSS. Results: total 264 (80.3% urban and 19.7% rural background) patients with mean age of 42 years with different educational level participated in the study. 1.1% patients were underweight, 2.7% mean BMI of studied population was 34.76. BMI distribution curve was bilaterally symmetrical. No one in the study population was well aware of about the BMI and related comorbidities. 98.5% patients confirmed that their doctor had never discussed their BMI with them. Conclusion: There is a significant gap of knowledge among patients regarding obesity and BMI, and physicians also have to take initiatives to discuss about this for primary control of the disease (obesity) and related comorbidities.